Pengaruh Metode Membaca Nyaring Terhadap Penguasaan Kosakata Bahasa Indonesia Pada Murid Kelas IV SDN 164 Inpres Lappawarue Kecamatan Mallawa Kabupaten Maros - Nursyahada Nursyahada; Amal Akbar; Besse Syukroni (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The main problem in this research is whether there is an influence of the reading aloud method on the mastery of Indonesian vocabulary in class IV students at SDN 164 Inpres Lappawarue, Mallawa District, Maros Regency. This research aims to describe the effect of applying the reading aloud method on the mastery of Indonesian vocabulary in class IV students at SDN 164 Inpres Lappawarue, Mallawa District, Maros Regency.This type of research is Pre-Experimental. The research design is a pretest-posttest design, namely an experiment which in its implementation only involves one class as an experimental class without a comparison class (control class). The subjects used in this research were 11 students.The results of descriptive statistical analysis of the use of the Reading Aloud Method on Mastery of Indonesian Vocabulary are positive, mastery of Indonesian vocabulary using the Reading Aloud method shows better vocabulary mastery than before the Reading Aloud method was applied. The results of inferential statistical analysis using the t test formula show that the calculated t value obtained is 6.097 with a frequency of db = 30–1 = 29, at a significance level of ???? = 0.05, t table = 2.228. So, t count > t table or the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This proves that there is an influence in implementing the Reading Aloud method on the Mastery of Indonesian Vocabulary in Class IV Students at SDN 164 Inpres Lappawarue, Mallawa District, Maros Regency